A preliminary concrete mixture design based on fracture toughness - Ince, Ragip; Bildik, Abdullah Tevfik (Springer, 2021)
The calculations of the mixture design of concrete have been widely performed according to the compressive strength or tensile strength. However, a cracked concrete/reinforced concrete structure can only be simulated by using the principles of fracture mechanics. The purpose of this study is to obtain certain expressions based on the properties of the fresh concrete and the fracture toughness of concrete, which is the fundamental parameter in analysis of the cracked structures. In accordance with this aim, the concrete mixture design method with the monogram proposed by Monteiro et al. for cement-based materials was utilized. Accordingly, 28 sets of batches with different slump values, cement contents, and water/cement ratios were cast to obtain this monogram. Fracture toughness tests on the notched beams and wedge-splitting (WS) specimens, and compression and splitting tests on cubes were conducted for hardened concrete. The fracture toughness test results were analyzed according to the effective crack model (ECM) in concrete fracture. Consequently, a mix design approach with a monogram was proposed to design according to the fracture mechanics of concrete. Furthermore, an approach based on the WS test was initially suggested to determine the fracture toughness of concrete for the ECM, which was essentially based on beams.
Keywords: Concrete; Effective crack model; Fracture toughness; Mix design; Strength